The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00423-011-0822-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life is not influenced by the extent of surgery in patients with benign goiter

Abstract: Thyroid surgery can be done safely and without impairment of life quality, regardless of the extent of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…A recently published study showed that the extent of thyroidectomy did not influence the QoL [20]. However, Values for variables found significant on multivariate analysis are in italics and in parentheses a Only significant correlation listed we noticed that patients who underwent total thyroidectomy had significantly better swallowing-related QoL than those who underwent hemithyroidectomy, though obviously the indications for the procedures would be different.…”
Section: Discussionmentioning
confidence: 79%
“…A recently published study showed that the extent of thyroidectomy did not influence the QoL [20]. However, Values for variables found significant on multivariate analysis are in italics and in parentheses a Only significant correlation listed we noticed that patients who underwent total thyroidectomy had significantly better swallowing-related QoL than those who underwent hemithyroidectomy, though obviously the indications for the procedures would be different.…”
Section: Discussionmentioning
confidence: 79%
“…Another important issue that could modify/influence both surgeon and patient choice in favor of a surgical option is the assessment of the QoL after thyroidectomy. Prior studies indicated that surgery extent does not influence the QoL [38] and the specific symptom Btiredness^remains one of the most affected domains [39][40][41] after thyroidectomy. It should be noted that in these studies both TT and HT are considered together.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the effects of treatment of nontoxic goiters on QOL, using well‐validated instruments, are few and show conflicting results . Using generic questionnaires, Short Form Health Survey‐36 and EuroQOL‐5D questionnaires, 2 studies found no improvements in QOL after thyroid surgery . A concern aired regarding these results was the possible low sensitivity of generic questionnaires in general.…”
Section: Introductionmentioning
confidence: 99%